2022
DOI: 10.1111/ejn.15865
|View full text |Cite
|
Sign up to set email alerts
|

Test–retest reliability of a finger‐tapping fMRI task in a healthy population

Abstract: Measuring brain activity during functional MRI (fMRI) tasks is one of the main tools to identify brain biomarkers of disease or neural substrates associated with specific symptoms. However, identifying correct biomarkers relies on reliable measures. Recently, poor reliability was reported for task-based fMRI measures. The present study aimed to demonstrate the reliability of a finger-tapping fMRI task across two sessions in healthy participants. Thirtyone right-handed healthy participants aged 18-60 years took… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…Only large differences in movement characteristics (e.g., 25% and 75% MVC) result in significant activation changes. Additionally, work by Wüthrich et al 88 recently observed good fMRI activation overlap and reliability between sessions with a finger tapping task, even between conditions where pacing was fast unpaced or paced. Regardless we believe such differences are unlikely to occur in this study, as participants were instructed to perform the movements at a comfortable self-selected pace, without any additional resistance.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Only large differences in movement characteristics (e.g., 25% and 75% MVC) result in significant activation changes. Additionally, work by Wüthrich et al 88 recently observed good fMRI activation overlap and reliability between sessions with a finger tapping task, even between conditions where pacing was fast unpaced or paced. Regardless we believe such differences are unlikely to occur in this study, as participants were instructed to perform the movements at a comfortable self-selected pace, without any additional resistance.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Dice coefficients were then calculated to quantify the overlap in each contrast: activation (sexual > control) = 0.601, deactivation (control > sexual) = 0.643. As stated by Wüthrich et al 12 , there is a lack of consensus regarding the interpretation of Dice coefficients. However, as proposed by Wüthrich 12 , we followed the guidelines set out by Cicchetti 13 .…”
Section: Resultsmentioning
confidence: 99%
“…As stated by Wüthrich et al 12 , there is a lack of consensus regarding the interpretation of Dice coefficients. However, as proposed by Wüthrich 12 , we followed the guidelines set out by Cicchetti 13 . Coefficients below 0.40 are considered poor; between 0.40 and 0.59, fair; between 0.60 and 0.74, good, and > 0.75, excellent.…”
Section: Resultsmentioning
confidence: 99%
“…Participants' error correction ability was assessed with a finger tapping task (Fig. 2a) Vishne et al, 2021;Wüthrich et al, 2022). Finger tapping shows good behavioral robustness, test-retest reliability, and consistent activation of error correction networks in the brain, such as the cerebellum, the supplementary motor area, and the prefrontal cortex (Carey, Abbott, Egan, Tochon-Danguy, & Donnan, 2000;Edagawa & Kawasaki, 2017;Wüthrich et al, 2022).…”
Section: Finger Tapping Taskmentioning
confidence: 99%